EFEKTIVITAS METODE NURUL BAYAN DALAM PENINGKATAN HASIL BELAJAR AL-QUR’AN - Faizah, Ade; Muh. Ubaidillah Alghifary Slamet; Sri Widyastri (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
This study aims to evaluate the effectiveness of the Nurul Bayan method in improving Quran learning outcomes among early childhood students at Sekolah Hafiz Qur'an, Ciputat, South Tangerang. The Nurul Bayan method is a teaching approach specifically designed to facilitate the understanding and memorization of Quranic verses through structured and systematic learning techniques. This research uses an experimental design with a sample of 60 early childhood students divided into two groups: an experimental group using the Nurul Bayan method and a control group using conventional teaching methods. Data were collected through pre-tests and post-tests to measure improvements in Quran learning outcomes. The results showed a significant improvement in Quran learning outcomes in the group using the Nurul Bayan method compared to the control group. The post-test average scores of the experimental group were significantly higher than those of the control group, indicating that the Nurul Bayan method is more effective in enhancing the understanding and memorization of Quranic verses. Additionally, student responses to this method were positive, with many reporting that it made learning the Quran more interesting and easier to understand. In conclusion, the Nurul Bayan method has proven effective in improving Quran learning outcomes among early childhood students. The use of this method can be a good alternative for educators in teaching the Quran, helping young students to better understand and memorize Quranic verses. The recommendation from this study is to expand the use of the Nurul Bayan method in various Islamic educational institutions to enhance the quality of Quranic education for early childhood.